Perceived learning outcomes of a short-term collaborative learning program: Toward developing intercultural competence and equitable Global North‒South partnerships - Shimoyamada, Sho (Journal of International Students, 2026)
This study investigated Japanese students’ perceived learning outcomes from a short-term program jointly conducted by the University of Tokyo and Asian University for Women in Bangladesh through the lens of intercultural competence and the contact hypothesis. Qualitative data were derived primarily from Japanese students’ essays. Inductive analysis revealed that intergroup interactions enhanced Japanese students’ awareness of social inequalities, diverse ethnic identities, prevailing stereotypes against the Global South, their own privilege, and Japan’s colonial legacy. This study makes theoretical contributions by illuminating the potential for inappropriate and ineffective interactions with outgroup peers. These findings suggest that educators should create environments where learners feel safe in making communicative mistakes and avoid hastily developing learners’ intercultural competence.